Lexical and Discursive Construction of Identity in Selected Twenty-First Century Nigerian Novels (2013)
Construction of identity constitutes a major means by which novelists, dramatists and poets deal with the interface between themes and social realities in their writings. Given the centrality of this engagement to literary discourse, elaborate attention has been given to identity construction in most literary genres, especially, poetry, drama and autobiographies. However, inadequate attempt has been made to explore the role of contextualized vocabulary choices in identity discourse in the novel, which contains clearer and more elaborate testimonies of identity construction than other literary genres. This study, therefore, investigates lexical and discursive construction of identity in selected twenty-first century Nigerian novels in terms of forms and lexico-discursive features. This is with a view to determining how identity is indexicated in the novels. The study adopted aspects of Ruth Wodak‘s discourse-historical analysis, together with lexical semantics and Manuel Castells‘ identity theory. Four Nigerian novels were purposively sampled: two Nigeria-based authors: Abimbola Adelakun‘s Under the Brown Rusted Roofs [RR] and Vincent Egbuson‘s Love My Planet [LP]; and two foreign-based authors: Helon Habila‘s Waiting for an Angel [WA] and Okey Ndibe‘s Arrows of Rain [AR]. Habila‘s and Egbuson‘s award-winning novels were sampled over their other novels, while Adelakun‘s and Ndibe‘s only novels were respectively selected. The texts were selected because they manifest issues relating to identity construction. The language of the novels was subjected to lexical and discursive analyses. Four forms of identities – national, ethnic, social, and religious – manifested in the novels. National identity bifurcates into cultural sameness and uniqueness – lexicalized through borrowing and innovations and politics, characterised by indigenous abbreviations. Ethnic identity, indexed through borrowing and naming, is laden with conflictual and antagonistic moves, indicating resistance to the outgroup. Three types of social identities are negotiated: professional, ingroup and outgroup. Professional identity is lexicalised through borrowing from Spanish, Latin and French, and Nigerian Pidgin; ingroup identity indexicated by emotive slangy expressions; and outgroups by naming and euphemisms that are replete with disaffiliating strategies. Three forms of religious identities, constructed through religious expressions, manifested: legitimising, resistance and powerlessness. Legitimising and resistance identities are respectively characterised by domineering and resistant discourse moves and powerlessness by attitudinal indexes, effusive and affiliating mappings. Sexual identity, constructed through naming, slangy and euphemistic expressions, are contested on the discursive strategies of inclusion and exclusion marked by tagging, subversive and aggressive moves. While the religious expressions in LP, AR and WA encode Christian identity, RR‘s exploration of Arabic expressions constructs Islamic identity. Although LP and WA borrow extensively across indigenous languages to legitimise national identity and ethnic identity construction, evident in elaborate adoption of Yoruba and Igbo expressions, there are no significant differences in their choices of lexicodiscursive features. Twenty-first century Nigerian novelists deploy lexico-discursive features in the construction of identity forms; beliefs, religion and education play significant roles in the construction of identity. These demonstrate an exquisite interplay of form and function elements in the construction of identity in the Nigerian novel